Organizational neuroscience - Waldman, David A. 1955-; Balthazard, Pierre A. (Emerald, 2015)
The goal of this book is to introduce organizational researchers and practitioners to the role of neuroscience in building theory, research methodologies and practical applications. On one hand, we aim to be a useful resource for researchers who look to become more familiar with organizational neuroscience or incorporate its concepts and methods into their own research. On the other hand, we provide insight for practitioners, who can envision neuroscience applications as a means of expanding their own professional toolboxes. The book is in two sections. First, we introduce general issues that cover the domain of organizational neuroscience, including the nature of the overall field and theoretical and methodological considerations. This section also addresses practical implications, especially for development processes. Second, we explore neuroscience influences on certain topics, such as leadership, emotion/affect, teams, ethics and moral reasoning and organizational justice. We conclude by pondering the future of organizational neuroscience; including ethical, social and legal issues, as well as the potential limitations of this emerging field.
Keywords: Neurosciences.; elektronické knihy; electronic books